Jesus de Nazaré e a tributação romana: empobrecimento, endividamento e o impacto no ambiente dos camponeses a partir de Marcos 12,13-17 - Silva, Hamilton Castro da (2017)
This dissertation was carried out with the objective of presenting the sociohistorical environment of Palestine in the first century, in which Jesus of Nazareth lived, in order to perceive its impacts on the praxis of Jesus, specifically in relation to Roman taxation. We will observe the dominant elites, represented by the Roman Empire, by the family of Herod and by the high priests of the Temple in Jerusalem. These elites, through a system of patronage, exerted a strong economic domination by means of a high tax burden on the peasants. With this, they produced, within the peasantry environment, great indebtedness, loss of property and the destruction of the family. The research sought to demonstrate that historical Jesus is the result and a proposed solution to a situation of economic exploitation in rural villages and towns of Palestine in the first century. The dissertation seeks to present the reaction of Jesus of Nazareth to Roman taxes, analyzing the text of Mark 12: 13-17, specifically the saying of Jesus in v. 17, which states: "Return to Caesar the things of Caesar and to God the things of God." The research shows that this saying indicates that Jesus took a critical stance regarding the payment of taxes to the Romans in favor of the removal of the Roman Empire coins from the lands of Israel. The research shows that the attitude of the historical Jesus against Roman taxes is motivated by a nationalistic and scriptural zeal based on the biblical statement in Leviticus 25:23: "The land [Israel] is mine, says the Lord." In this way, Jesus of Nazareth, guided by this nationalistic zeal, presents an ethical proposal based on biblical and apocalyptic traditions, confronting the tyrannical control and abuse of power by the Roman Empire, that is: The ethics of presenting a praxis of option for the little ones, surpassing the regimes of oppression and tyranny.